Os estilos cognitivos na educação escolar e sua dimensão conceitual como aporte teórico para a orientação do ensino e da aprendizagem - Lemes, Sebastiao de Souza [UNESP] (My University, 2012)
The contributions of studies on Cognitive Styles are presented and discussed in this text, introductory and conceptually, in order to clarify and facilitate the discussion within the school education. With the theoretical origin in the cognitive psychology, more specifically, in studies of human cognition in differential perspective, the Cognitive Styles, are constructs developed to describe perceptual characteristics of the individual called "Dependence and Independence Field." In the course of this conceptual construction it is evidenced that individual perceptions are part of a broad set of interrelated factors that reflect the level of psychological differentiation of individuals. The studies show subjects with different Cognitive Styles, that are distributed in a "continuum" in order to set up a statistical normality. Therein some educational implications related to the Cognitive Styles are evident in relation to how the students learn, how the teachers teach, to the formal education in itself and to the career plan. The Cognitive Styles has a broad spectrum of influence on the relationship established in the teaching-learning process. So, these concepts need urgently to be better understood in the context of education.

As contribuições dos estudos sobre Estilos Cognitivos (EC) são apresentadas e discutidas neste texto, de forma conceitual e introdutória, com o objetivo de esclarecer e possibilitar esse debate no âmbito da educação escolar. Com origem teórica na Psicologia Cognitiva, mais especificamente, nos estudos sobre cognição humana na perspectiva diferencial, os EC, são constructos desenvolvidos para descrever traços perceptuais dos indivíduos com denominação de “Dependência e Independência de Campo”. Na trajetória dessa construção conceitual encontram-se evidências de que as percepções individuais são parte de um conjunto amplo de fatores inter-relacionados que refletem o nível de diferenciação psicológica dos indivíduos. Os estudos mostram os sujeitos com diferentes EC, estão distribuídos em um “continuum” de forma a configurar uma normalidade estatística. Nesse sentido algumas implicações educativas relacionadas aos EC são evidenciadas em relação a como aprendem os alunos, como ensinam os professores, à educação formal em si e ao planejamento da carreira profissional. Os EC têm um largo espectro de influência nas relações que se estabelece no processo ensino-aprendizagem, por isso esses conceitos precisam urgentemente ser mais bem compreendidos no contexto educacional.
The cognitive styles in schooling and its conceptual dimension as theoretical orientation to teaching and learning: an introductory discussion
Keywords: Cognitive styles; Teaching-learning process and academic performance; Estilos cognitivos; Ensino-aprendizagem e desempenho acadêmico